The influence of respiratory muscle training upon intermittent exercise performance - Nicks, C. R.; Morgan, D. W.; Fuller, D. K.; Caputo, J. L. (International Journal of Sports Medicine, 2009)
The purpose of this study was to determine the effect of respiratory muscle training (RMT) on intermittent exercise performance, respiratory muscle strength (PImax), respiratory muscle fatigue (RMF), and dyspnea in soccer athletes. Collegiate soccer athletes (20 male, 7 female) were randomly divided into either a RMT or control condition during off-season conditioning. The RMT group performed a 30RM protocol (10 times weekly) for 5 weeks using a commercially-available training device, while the controls received no RMT. Performance was evaluated utilizing Level 1 of the Yo-Yo Intermittent Recovery Test (IRT) and dyspnea was assessed during and immediately following the IRT. RMF was quantified within 2 minutes (RMF2) and 10 minutes (RMF10) after completing the IRT. Following training, the RMT group significantly increased IRT performance by 216.6 ± 231.0 meters (p = .008) while the 49.2 ± 75.1 meter increase observed in the controls was not significant. PImax in the RMT group increased from 138.1 ± 19.6 to 165.3 ± 23.5 cmH2O (p < .001), with no significant change observed in the controls. RMT did not significantly affect RMF or dyspnea. In conclusion, RMT improved intermittent exercise performance in these soccer athletes. The mechanisms by which RMT improves performance warrant further study.